Notes on the Vertebrates of northern Pará, Brazil: a forgotten part of the Guianan Region, I. Herpetofauna - Avila-Pires, Teresa Cristina Sauer; Hoogmoed, Marinus Steven; Rocha, Wáldima Alves da (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
We discuss the herpetological results of seven expeditions to the Guianan part of Pará, which resulted in a total of 80 species of amphibians (77 frogs and three caecilians) and 95 species of reptiles (36 species of lizards, three species of amphisbaenians, 49 species of snakes, five species of chelonians and two species of caiman). We report six species new to science (three frogs, one caecilian, one lizard, one amphisbaenian), six new records for Brazil (five frogs, one caecilian) and 23 new records for Pará (13 frogs, four lizards, six snakes). For each of the new records we provide comments. Special comment is made about a large population of the toad Atelopus hoogmoedi that seems to be doing well and does not show any signs of population decline as many species of Atelopus at higher elevations do. We provide a complete list of species collected per locality containing data on endemicity, habitat, reproduction and food. For each of the seven collecting sites we provide data on richness and abundance of species. The sites are compared regarding their species composition, even though we can not say how much of the differences are due to specific habitats or geographic variation, seasonal variation or sampling deficiency. We synonymised the Bufonid Rhinella martyi with Bufo margaritifer and selected a lectotype for Rana margaritifera in order to resolve the problems about this name.